Near panmixia at the distribution‐wide scale but evidence of genetic differentiation in a geographically isolated population of the Terek Sandpiper Xenus cinereus. (10th August 2018) - Rönkä, Nelli; Pakanen, Veli‐Matti; Blomqvist, Donald; Degtyaryev, Victor; Golovatin, Mikhail; Isakov, Gennady; Karlionova, Natalia; Lehikoinen, Aija; Morozov, Vladimir; Paskhalny, Sergey; Pauliny, Angela; Pinchuk, Pavel; et al.
Abstract : Populations from different parts of a species range may vary in their genetic structure, variation and dynamics. Geographically isolated populations or those located at the periphery of the range may differ from those located in the core of the range. Such peripheral populations may harbour genetic variation important for the adaptive potential of the species. We studied the distribution‐wide population genetic structure of the Terek Sandpiper Xenus cinereus using 13 microsatellite loci and the mitochondrial DNA (mtDNA) control region. In addition, we estimated whether genetic variation changes from the core towards the edge of the breeding range. We used the results to evaluate the management needs of the sampled populations. Distribution‐wide genetic structure was negligible; the only population that showed significant genetic differentiation was the geographically isolated Dnieper River basin population in Eastern Europe. The genetic variation of microsatellites decreased towards the edge of the distribution, supporting the abundant‐centre hypotheses in which the core area of the distribution preserves the most genetic variation; however, no such trend could be seen with mtDNA. Overall genetic variation was low and there were signs of past population contractions followed by expansion; this pattern is found in most northern waders. The current effective population size ( N e ) is large, and therefore global conservation measures are not necessary. However, the marginal Dnieper River population needs to be considered its own management unit. In addition, the Finnish population warrants conservation actions due to its extremely small size and degree of isolation from the main range, which makes it vulnerable to genetic depletion.